The role of academic self-efficacy and school well-being on adjustment of first year university student - Utomo, Rizqy Cahyo; Andayani, Budi (Psychological Research and Intervention, 2023)
Adjustment of first year college student is argued as one of the hardest adjustment of a student in their lifetime. This quantitative study examines the contribution of academic self-efficacy toward their adjustment, moderated by their subjective perception of their educational institution's well-being, named as school well-being. Research would be conducted using three scales (adjustment scale, academic self-efficacy scale, and school well-being scale), in a real setting. Participants were 451 students from 9 department of Faculty S, one of faculty from one of the most prestigious university in Yogyakarta, Indonesia. The hypothesis was school well-being and academic self-efficacy would predict the successfulness of first year adjustment. Our findings conclude that school well-being and academic self-efficacy both predicts the score of student's adjustment. Academic self-efficacy contributes 32,29% of first year college student's adjustment, and ScWB contributes another 15,68% of it.